Sources of exposure identified through structured interviews of healthcare workers who test positive for severe acute respiratory coronavirus virus 2 (SARS-CoV-2): A prospective analysis at two teaching hospitals - Chanu Rhee; Meghan A. Baker; Robert Tucker; Diane Griesbach; Dinah McDonald; Sarah A. Williams; Karen Fiumara; Andrew Resnick; Michael Klompas; for the CDC Prevention Epicenters Program (Cambridge University Press, 2021)
We interviewed 1,208 healthcare workers with positive SARS-CoV-2 tests between October 2020 and June 2021 to determine likely exposure sources. Overall, 689 (57.0%) had community exposures (479 from household members), 76 (6.3%) had hospital exposures (64 from other employees including 49 despite masking), 11 (0.9%) had community and hospital exposures, and 432 (35.8%) had no identifiable source of exposure.